New TOEIC : - Koo, Jay (Tổng hợp Thành phố Hồ Chí Minh, 2011)
Nội dung sách gồm các phần: Read a text aloud, describe a picture, respond to questions, respond to questions using information provided, propose a solution, express an opinion.